Exploitation Minière, Facteur De Recompositions Socio-Economiques Dans La Sous-Préfecture De Hiré (Côte d’Ivoire) - Nicolas, Kouadio Kouassi (European Scientific Journal, ESJ, 2016)
Expected as a development opportunity, the construction of the mine of Bonikro (sub-prefecture of Hiré), has led to significant changes in the life of the local communities. In an initial context marked by a dynamic economy focused on agriculture, the implantation of the mining industry has not only generated new opportunities, but also economic constraints in the face of which local communities have developed adaptation strategies which have led locally to socio-economic reconstruction. The present study attempts to reveal these new behaviors and to analyze the logic which underlies them.